2022
DOI: 10.52711/0974-360x.2022.00838
|View full text |Cite
|
Sign up to set email alerts
|

Chemically synthesized Schiffs base Conjugated Piperonal as novel Antioxidants and Scavengers of Free Radicals

Abstract: Ethylene diamine is an organic compound which is a strongly basic amine and is used to conjugate Piperonal, an heterocyclic aldehyde. The ethylene diamine conjugated piperonal was prepared using simple method and the antioxidant assays like DPPH, ABTS, Ferric reducing assay and several other methods were carried out through in vitro assays. The experiments were carried out with unconjugated piperonal and compared with the activity shown by the test sample. The overall result shows a good antioxidant effect whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The structure of piperonal forms the basis for the synthesis of various chalcones and flavonoids. The study reported potent antioxidant free radical scavenging potential of piperonal and EDP schiffs base linked piperonal 14 . However, the piperonal and its structural analogues were not explored for the down regulation of VEGFR targeting angiogenesis.…”
Section: Introductionmentioning
confidence: 91%
“…The structure of piperonal forms the basis for the synthesis of various chalcones and flavonoids. The study reported potent antioxidant free radical scavenging potential of piperonal and EDP schiffs base linked piperonal 14 . However, the piperonal and its structural analogues were not explored for the down regulation of VEGFR targeting angiogenesis.…”
Section: Introductionmentioning
confidence: 91%